Analysis Of The Leadership Concept Of Maximus In The Movie Gladiator (2000) Using The Swot Theory Approach - Bayu Ade Prabowo; Henry Yuliamir; Umar Abdul Jabbar (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Through the application of the SWOT theory, this study examines the leadership concept that Maximus portrays in the movie Gladiator (2000). The objective of this study is to determine the factors that influence the leadership of the primary protagonist, specifically focusing on their strengths, weaknesses, opportunities, and threats. The research methodology used in this study is a comprehensive examination of Maximus' behaviors and attributes as depicted in the film. The findings of the analysis indicate that Maximus possesses notable attributes in the realm of moral leadership and courage, which significantly contribute to his achievements within the film. Nevertheless, it is important to acknowledge that he possesses certain limitations, including a tendency for uncertainty and vulnerability. Moreover, Maximus draws on the chances presented by the establishment of friendships and the provision of support from other characters, ultimately enabling him to accomplish his objectives. The principal sources of danger arise from the protagonist's antagonists within the narrative. In summary, the leadership philosophy shown by Maximus in the film Gladiator can be seen as embodying the fundamental elements of the SWOT analysis framework. The findings of this analysis contribute to our comprehension of leadership dynamics within the framework of a cinematic story and offer valuable perspectives on the use of SWOT theory in the examination of fictional personas. The results mentioned above hold significance for comprehending leadership principles within the realm of popular culture and in the context of ordinary society.